1999
DOI: 10.1136/thx.54.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and home environment in children: a national survey

Abstract: Background-Respiratory diseases are common in childhood and may lead to chronic disease in adult life; environmental factors probably play an important part in their causation. Methods-A survey of respiratory symptoms in children aged 12-14 years was conducted throughout Great Britain as part of the International Study of Asthma and Allergies in Childhood (ISAAC). Information was obtained on certain aspects of the home environment in order to assess their importance as risk factors. Results-The response rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
86
1
13

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 31 publications
13
86
1
13
Order By: Relevance
“…Los estudios de prevalencia de esta enfermedad muestran cifras entre 0,5 y 42% [11][12][13][14]25,26 , lo que depende especialmente de la edad y forma como se realiza el diagnóstico (definición operacional de …”
Section: N V E S T I G a C I ó Nunclassified
See 1 more Smart Citation
“…Los estudios de prevalencia de esta enfermedad muestran cifras entre 0,5 y 42% [11][12][13][14]25,26 , lo que depende especialmente de la edad y forma como se realiza el diagnóstico (definición operacional de …”
Section: N V E S T I G a C I ó Nunclassified
“…En nuestro estudio se observó una mayor prevalencia de SR en hogares con cubrepiso o alfombra, y mayor prevalencia de DR cuando había fumadores y calefacción a gas en el hogar. La asociación con la presencia de tabaquismo intradomiciliario y combustibles inusuales había sido descrita por Burr y cols 26 y von Mutius y cols 11 .…”
Section: N V E S T I G a C I ó Nunclassified
“…It has been suggested that the environment plays an important role in respiratory symptoms and it has been reported in traditional studies that chemicals, such as VOCs and formaldehyde generated in the environment and tobacco smoke, are potential risk factors for respiratory diseases (Wieslander et al, 1997;Norback et al, 1995;Burr et al, 1999). However, the influence of VOCs and formaldehyde on childhood asthma is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air pollution is of great importance since subjects in industrialized countries spend over 80% of their time indoors. It includes domestic allergens and indoor gas pollutants (695)(696)(697)(698), among which tobacco smoke is the major source (699).…”
Section: Pollutantsmentioning
confidence: 99%